LEGAL RESPONSIVENESS IN WASTE MANAGEMENT TO ADDRESS THE ENVIRONMENTAL CRISIS BASED ON SATJIPTO RAHARDJO’S RESPONSIVE LAW THEORY - Rahmalillah, Apriliani; Syamsuddin, Syamsuddin (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study examines the responsiveness of Indonesia’s legal framework in addressing the escalating waste management crisis through the perspective of Satjipto Rahardjo’s responsive law theory. Waste has emerged as a multidimensional environmental issue influenced by population growth, consumption patterns, and limited waste processing capacity. Although Law No. 18 of 2008 provides a normative foundation for integrated waste management, its implementation remains inconsistent and often disconnected from social realities. This research analyzes gaps between regulation and practice, particularly regarding public participation, institutional coordination, and infrastructure readiness. Using a normative–qualitative legal method with statutory, conceptual, and socio-legal approaches, the study evaluates how responsive law principles can strengthen waste governance. The findings show that Indonesia’s waste regulations have not fully embodied responsiveness, as communities are still treated primarily as objects rather than active partners, and local initiatives are not optimally integrated into policy. This study proposes a model of ecological responsiveness, emphasizing adaptive regulation, community empowerment, and collaborative governance. These recommendations contribute to developing a more effective and sustainable legal framework capable of addressing environmental challenges.